A Review of Current Advances in Ammonia Combustion from the Fundamentals to Applications in Internal Combustion Engines - Ma, Fei; Guo, Lingyan; Li, Zhijie; Zeng, Xiaoxiao; Zheng, Zhencao; Li, Wei; Zhao, Feiyang; Yu, Wenbin (Energies (Basel), 2023)
The energy transition from hydrocarbon-based energy sources to renewable and carbon-free energy sources such as wind, solar and hydrogen is facing increasing demands. The decarbonization of global transportation could come true via applying carbon-free fuel such as ammonia, especially for internal combustion engines (ICEs). Although ammonia has advantages of high hydrogen content, high octane number and safety in storage, it is uninflammable with low laminar burning velocity, thus limiting its direct usage in ICEs. The purpose of this review paper is to provide previous studies and current research on the current technical advances emerging in assisted combustion of ammonia. The limitation of ammonia utilization in ICEs, such as large minimum ignition energy, lower flame speed and more NOx emission with unburned NH3, could be solved by oxygen-enriched combustion, ammonia–hydrogen mixed combustion and plasma-assisted combustion (PAC). In dual-fuel or oxygen-enriched NH3 combustion, accelerated flame propagation speeds are driven by abundant radicals such as H and OH; however, NOx emission should be paid special attention. Furthermore, dissociating NH3 in situ hydrogen by non-noble metal catalysts or plasma has the potential to replace dual-fuel systems. PAC is able to change classical ignition and extinction S-curves to monotonic stretching, which makes low-temperature ignition possible while leading moderate NOx emissions. In this review, the underlying fundamental mechanism under these technologies are introduced in detail, providing new insight into overcoming the bottleneck of applying ammonia in ICEs. Finally, the feasibility of ammonia processing as an ICE power source for transport and usage highlights it as an appealing choice for the link between carbon-free energy and power demand.